2015
DOI: 10.1126/scitranslmed.aaa1652
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a plant isoflavonoid that causes biliary atresia

Abstract: Biliary atresia (BA) is a rapidly progressive and destructive fibrotic disorder of unknown etiology affecting the extrahepatic biliary tree of neonates. Epidemiological studies suggest that an environmental factor, such as a virus or toxin, is the cause of the disease, although none have been definitively established. Several naturally occurring outbreaks of BA in Australian livestock have been associated with the ingestion of unusual plants by pregnant animals during drought conditions. We used a biliary secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
151
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(155 citation statements)
references
References 72 publications
4
151
0
Order By: Relevance
“…Recently, the rare isoflavonoid 1,2diaryl-2-propenone present in Dysphania was the plant compound implicated in the development of BA, and was thus termed biliatresone. Biliatresone was found to cause selective destruction of the extrahepatic, but not intrahepatic, biliary system of larval zebrafish [44]. In addition to Dysphania, biliatresone is produced in human intestine from the bacterial metabolism of genistein [45].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the rare isoflavonoid 1,2diaryl-2-propenone present in Dysphania was the plant compound implicated in the development of BA, and was thus termed biliatresone. Biliatresone was found to cause selective destruction of the extrahepatic, but not intrahepatic, biliary system of larval zebrafish [44]. In addition to Dysphania, biliatresone is produced in human intestine from the bacterial metabolism of genistein [45].…”
Section: Discussionmentioning
confidence: 98%
“…In human fetuses, bile acid synthesis occurs during the early organogenesis stages, during which bile starts to be excreted into the intestine near the end of the first trimester (Nakagawa and Setchell, 1990 and references therein). Furthermore, recent studies of naturally occurring outbreaks of sheep biliary atresia revealed that biliatresone, a causative toxin for biliary atresia, reduces Sox17 expression levels in the bile duct epithelia, and that silencing Sox17 mimics the effects of biliatresone on the bile duct epithelia (Lorent et al, 2015;Waisbourd-Zinman et al, 2016). Together with the extensive anatomical similarity of the extrahepatic biliary tracts and the associated blood vessels, nerves and smooth muscles between mice and humans (Higashiyama et al, 2016), the Sox17 +/− mouse embryo provides a useful experimental model with which to study the initial pathogenesis of biliary atresia.…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish, the intrahepatic biliary network is formed by small-diameter ductular biliary epithelial cells, which might be analogous to small-diameter ductular biliary epithelial cells in the mammalian liver lobule that transport bile from the canalicular network to the intralobular bile ducts in the portral tract (Kaneko et al, 2015). Indeed, there is remarkable conservation of both genes and gene function across vertebrate biliary system development, and thus many candidate genes responsible for biliary system abnormalities in humans can be screened efficiently and rapidly in the zebrafish model Delous et al, 2012;Hand et al, 2009;Lorent et al, 2015Lorent et al, , 2010Lorent et al, , 2004Matthews et al, 2011Matthews et al, , 2005Sakaguchi et al, 2008;Schaub et al, 2012). The zebrafish transgenic line Tg(Tp1-MmHbb: EGFP) um14 , which is generated by conjugating tandem RBPJκ response element repeats with enhanced green fluorescent protein (EGFP), expresses EGFP specifically in the intrahepatic biliary network in the zebrafish liver (Lorent et al, 2010;Parsons et al, 2009).…”
Section: Introductionmentioning
confidence: 99%